Age‐related changes in miR‐143‐3p:Igfbp5 interactions affect muscle regeneration. Issue 2 (13th January 2016) - Soriano‐Arroquia, Ana; McCormick, Rachel; Molloy, Andrew P.; McArdle, Anne; Goljanek‐Whysall, Katarzyna
Summary: A common characteristic of aging is defective regeneration of skeletal muscle. The molecular pathways underlying age‐related decline in muscle regenerative potential remain elusive. microRNAs are novel gene regulators controlling development and homeostasis and the regeneration of most tissues, including skeletal muscle. Here, we use satellite cells and primary myoblasts from mice and humans and an in vitro regeneration model, to show that disrupted expression of microRNA‐143‐3p and its target gene, Igfbp5, plays an important role in muscle regeneration in vitro . We identified miR‐143 as a regulator of the insulin growth factor‐binding protein 5 (Igfbp5) in primary myoblasts and show that the expression of miR‐143 and its target gene is disrupted in satellite cells from old mice. Moreover, we show that downregulation of miR‐143 during aging may act as a compensatory mechanism aiming at improving myogenesis efficiency; however, concomitant upregulation of miR‐143 target gene, Igfbp5, is associated with increased cell senescence, thus affecting myogenesis. Our data demonstrate that dysregulation of miR‐143‐3p:Igfbp5 interactions in satellite cells with age may be responsible for age‐related changes in satellite cell function.